Dependence of O+ escape rate from the Venusian upper atmosphere on IMF directions. Issue 9 (12th May 2013) - Masunaga, K.; Futaana, Y.; Stenberg, G.; Barabash, S.; Zhang, T. L.; Fedorov, A.; Okano, S.; Terada, N.
Abstract [1] We investigate the dependence of the O+ escape rate on the upstream interplanetary magnetic field (IMF) direction by using data from the Analyser of Space Plasma and Energetic Atoms (ASPERA‐4) instrument and the magnetometer (MAG) onboard Venus Express. We consider two cases, namely the perpendicular IMF case (167 events) and the parallel IMF case (82 events), where IMF is nearly perpendicular to the Venus‐Sun line and nearly parallel to it. By integrating O+ fluxes observed on the nightside, total O+ escape rates of (5.8 ± 2.9) × 1024 s−1 (perpendicular IMF case) and (4.9 ± 2.2) × 1024 s−1 (parallel IMF case) are obtained. As these values are not significantly different, the upstream IMF direction does not affect the total amount of O+ outflow from Venus. The different acceleration mechanisms must balance each other in order to keep the escape rate the same.